Surya dalam Berita - Astuti, Santi Indra (FIkom Unisba, 2005)
For sure, Surya Paloh is a political figure prominent enough in Indonesia. As one of important member of Golkar, Surya Paloh famously known as the leader who often made manouvres—many of them considered as unpopular decisions for his party-mate. He often use his media—Metro TV and Media Indonesia (daily newspaper)—to support his political career. An analysis of Surya Paloh’s news in his daily become the evidence of this hypotheses. Surya Paloh depicted here with the newsmaker, from Sultan to Presidents and other political leaders. Media Indonesia, therefore, has framed Surya Paloh as one of the newsmaker to be considered in national politics.